PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI ( Studi Kasus Di Satuan Kerja Non Vertikal Tertentu Pengembangan, Pengendalian Dan Pelaksanaan Pekerjaan Strategis Bidang Pekerjaan Umum Dan Perumahan Rakyat Lainnya, Kementerian Pekerjaan Umum Dan Perumahan Rakyat) - Rudy Soelistio; Faroji Faroji; Uswatun Hasanah (JURNAL TEKNIK INDUSTRI, 2016)
Employee productivity sizes commonly used in providing employee assessment consists of thequantity that results achieved in carrying out the task. A third indicator is the quality. The quality ofthis dimension where quality shows how a task can be completed seen from the aspect of skill,precision and cleanliness. Other sizes are punctuality which includes attendance or absenteeism ofemployees and timeliness in completing the work. Some qualitative measures can be used as a tool todetermine how well an employee is working, especially that the government agency is in the form ofan agency that should be a model, of course, the quality of service becomes essential as the initialmeasure of success. The better performance of a government agency it is expected to transmit toagencies in other government to miningkatkan service quality. Likewise if an agency is not good willbe transmitted to other agencies to no good.Analysis is conducted quantitative analysis using linear regression to answer the problem formulationand determine the influence of the variables that have been determined. The results of this study arevery influential leadership style on employee performance. Besides the work attitude of employees isalso crucial to performance.